[I118] Active motion management strategies: Breath hold, gating, tracking. (August 2018) - Aznar, Marianne
Abstract : In this lecture, we will review active motion management strategies such as breath hold and gating. We will discuss patient selection and compliance, appropriate verification strategies and impact on dose distribution and planning target margins in various sites such as breast, lung or liver cancer and pediatrics. The solutions presented will range from equipment-free, pragmatic solutions to advanced technologies (tracking, MR linac).